Wave energy spectrum for the south China sea - Liew, M.S. (Society of Naval Architects and Marine Engineers, 2015)
Advances have been made in analysis of the wave energy spectrum for the South China Sea (SCS). Wave energy spectrum is the total energy distributed throughout the various wave components of studied waves. NALL (SCS) is the acronym of the derived wave energy spectrum for the Malaysian waters, NALL standing for Nasir Azmi Liew Lim. In initial attempts to address the SCS spectrum, it was found that the measured spectrum is closer to the joint North Sea wave project (JONSWAP) Goda spectrum. The recording machine used to measure the wave data is the Wave Radar REX, located at the edge of an off shore platform at a location that is dependent on the wave elevation from respective water levels. The wave sensors are part of the real-time monitoring system, which measures other physical parameters such as wind speed and sea current speed. Gaps and missing data are found throughout the data processing stage. The measured wave data was processed to ensure the integrity of the time series data through QC/QA procedures. It is essential that the length of the time series be ascertained. Thereafter, the time series is transformed in the frequency domain using Fourier Transform and the analyses of the wave energy spectrum is done. In the process flow, a final regional adjustment factor must be made to ensure that the derived local spectrum for the SCS in the operating oil blocks of the Malaysian waters is achievable.